Kreativitas Guru Memotivasi Peserta Didik dalam Pembelajaran PJOK di SD Negeri 1 Rumah Tiga - Selestina R Karmezach; J. Anaktototy; M. Souisa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Teacher creativity is an important factor in creating interesting Physical Education, Sports, and Health (PJOK) learning activities that can improve students’ learning motivation. Physical education learning in elementary schools requires strategies that match students’ characteristics so they can actively participate in physical activities. This study aims to describe the forms of physical education teacher creativity in motivating students and analyze its impact on students’ learning motivation at SD Negeri 1 Rumah Tiga. This research used a descriptive qualitative approach involving physical education teachers and fifth and sixth grade students as informants. Data collection techniques included observation, interviews, and documentation. Data analysis used an interactive model consisting of data reduction, data presentation, and conclusion drawing. The results showed that teacher creativity was reflected through game modification, variation of learning methods, utilization of simple equipment, movement demonstrations, verbal motivation, and the provision of praise and rewards. The discussion showed that teacher creativity created an enjoyable learning atmosphere that increased students’ activeness, enthusiasm, confidence, and participation. This study concludes that physical education teacher creativity plays an important role in improving students’ learning motivation through innovative, active, and meaningful learning experiences.